An extended crystal plasticity model to simulate the deformation behaviors of hybrid stress–strain controlled creep-fatigue interaction loading. (March 2022) - Zhou, Dewen; Wang, Xiaowei; Wang, Runzi; Zhang, Tianyu; Yang, Xinyu; Jiang, Yong; Zhang, Xiancheng; Gong, Jianming; Tu, Shantung
Highlights: Simulations of hybrid-controlled creep-fatigue interaction (HCFI) were performed. Simulated results of cyclic deformation matched well with the experimental data. Increase in computational time of the extended model was limited. Abstract: A numerical process based on crystal plasticity finite element method was implemented to describe the cyclic stress–strain response and especially the creep deformation of 9 %Cr steel under hybrid stress–strain controlled creep-fatigue interaction loading at 650 °C. An extended model based on Armstrong and Frederick (A-F) hardening law was used to capture the creep strain. Compared with experimental results, the creep strain performed by A-F model was small while extended model predicted well. The cyclic softening and decline tendency of relaxation have been simulated. Simulations of other loading modes with extended model also show a good agreement with experimental results.